Characteristics of Patients Experiencing Post-Spinal Anesthesia Shivering in the Elective Operating Room - Eppy Setiyowati; Eka Sulistyowati; Tri Sunu Probolaksono; Ragil Putri Fitriyana (GLOBAL HEALTH SCIENCE GROUP, 2026)
Post-spinal anesthesia shivering can cause discomfort, increased metabolism, heightened surgical wound pain, and serious complications such as increased oxygen consumption, CO₂ production, hypoxemia, lactic acidosis, and cardiac arrhythmias. This condition may also interfere with the interpretation of vital sign monitoring. This study aims to describe the characteristics of patients experiencing shivering in the elective operating rooms of RSUD dr. Mohamad Soewandhie Surabaya. The study focuses on factors such as age, gender, body mass index (BMI), operating room temperature, and duration of surgery. This research employed a descriptive design and used consecutive sampling, involving 101 post-spinal anesthesia patients who experienced shivering in the elective operating rooms of RSUD dr. Mohamad Soewandhie Surabaya. Data were collected using an observation checklist and analyzed descriptively in the form of frequency distribution and percentages. The results showed that the majority of patients were in the late elderly age group (56–65 years) (51.5%), male (63.4%), and had a normal BMI (73.3%). All patients were exposed to operating room temperatures below 20°C (very cold), and almost all surgeries lasted between 1–2 hours (79.2%). Operating room temperature was the most dominant factor.